Heat pain detection threshold is associated with the area of secondary hyperalgesia following brief thermal sensitization: a study of healthy male volunteers [Corrigendum] - Hansen MS; Wetterslev J; Pipper CB; Asghar MS; Dahl JB (Journal of Pain Research, 2017)
Hansen MS, Wetterslev J, Pipper CB, Asghar MS, Dahl JB.Journal of Pain Research. 2017;10:265–274.  On page 267, right column, 2nd paragraph, line 10, the first sentence under “Assessment of secondary hyperalgesia” should read “The area of secondary hyperalgesia was quantified after pinprick stimulation with monofilament (von Frey hair) with a nominal value of 18 (bending force of 490 mN) in 4 linear paths arranged 90° around the center of the thermode”.Read the original article